2021
DOI: 10.18608/jla.2021.7379
|View full text |Cite
|
Sign up to set email alerts
|

More Than Figures on Your Laptop: (Dis)trustful Implementation of Learning Analytics

Abstract: The adoption of learning analytics (LA) in complex educational systems is woven into sociocultural and technical challenges that have induced distrust in data and difficulties in scaling LA. This paper presents a study that investigated areas of distrust and threats to trustworthy LA through a series of consultations with teaching staff and students at a large UK university. Surveys and focus groups were conducted to explore participant expectations of LA. The observed distrust is broadly attributed to three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
(147 reference statements)
3
24
0
Order By: Relevance
“…This could indicate that the HEIs that were in the early stages of adoption were paying particular attention to smoothing out ethics and privacy issues or that they had concerns related to setting protocols for data sharing with external partners. An increasing number of studies have found that there are concerns raised in HEIs about sharing of student data with external stakeholders (Selwyn, 2019 ; Tsai et al, 2021b ). This concern should be addressed by setting a policy that safeguards stakeholders’ data from harmful use that can result from data sharing, especially in the preparation stage, as suggested above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate that the HEIs that were in the early stages of adoption were paying particular attention to smoothing out ethics and privacy issues or that they had concerns related to setting protocols for data sharing with external partners. An increasing number of studies have found that there are concerns raised in HEIs about sharing of student data with external stakeholders (Selwyn, 2019 ; Tsai et al, 2021b ). This concern should be addressed by setting a policy that safeguards stakeholders’ data from harmful use that can result from data sharing, especially in the preparation stage, as suggested above.…”
Section: Discussionmentioning
confidence: 99%
“…Typical stakeholders involved in LA in HEIs include students, teaching staff, institutional management, researchers, and developers (Drachsler & Greller, 2012 ; Khalil & Ebner, 2015b ; Tsai et al, 2018 , 2021b ). Stakeholders can be divided into clients and subjects (Drachsler & Greller, 2012 ; Kollom et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, LA practice and research increasingly stress LA's impact on learning (eg, Chen et al, 2018; Lang et al, 2022) and learning progression (eg, Gašević et al, 2022). Furthermore, although acceptability does not stand out as a term related to LA, it is reflected in the essential topics of trustworthiness (eg, Kitto & Knight, 2019; Tsai et al, 2021) and fairness (eg, Carter & Egliston, 2021; Coghlan et al, 2021; O'Neil, 2016; Selwyn, 2020) of LA. Finally, the aspect of cost is related, but not limited to sustainability of LA (Gašević et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, key stakeholders should be taken as an integral component of any learning analytics implementation (Tsai et al, 2018). This is most important considering the distrust teachers may develop towards data-driven implementations, attributed mostly to the subjective nature of numbers, the fear of power diminution, and approaches to design and implementation (Tsai et al, 2021); it was recently pointed out that such a tendency is particularly prominent when referring to preditions for students at-risk (Kollom et al, 2021). On the other hand, involving teachers in the early stages of learning analytics design, particularly engaging them with data collected on students, may improve their pedagogic and assessment practises, leading potentially to the development of more suitable learning analytics tools (Holstein et al, 2019;Vezzoli et al, 2020).…”
Section: Education Stakeholders' Engagement With Prediction Modelsmentioning
confidence: 99%